Biomol Potential from Vegetable Market and Tofu Factory Waste for Cleared Land Crops - Nourma Yulita; Mohammad Agus Prayitno; Sultan Ahmad Fausan (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2022)
This research was conducted in Cialam Caya Village, Konda Subdistrict, South Konawe Regency, in July - September 2021. The purpose of the study was to determine the effect of various doses of Biomol on the growth and yield of mustard greens. This study was arranged in a Randomized Block Design (RAK) which consisted of 7 treatments with biomol doses, namely: control (without biomol), P1 50 ml, P2 100 ml, P3 150 ml, P4 200 ml, P5 250 ml, P6 300 ml, 3-time treatment repetition to produce 21 experimental units. The results of this study concluded that the administration of biomol had a very significant effect on the growth and yield of mustard greens (plant height, number of leaves, fresh weight and dry weight) and the best dose of biomol for mustard greens (Brassica Juncea L.) was at a dose of 200 ml.